1991
DOI: 10.1139/e91-044
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb geochronology of Late Proterozoic rocks of the eastern Cobequid Highlands, Avalon Composite Terrane, Nova Scotia

Abstract: In the Cobequid Highlands of Nova Scotia, low-grade late Precambrian arc-related volcano-sedimentry rocks typical of the Avalon Composite Terrane overlie platformal metasedimentry rocks and are spatially associated with gneisses previously considered to be basement to both these units. U–Pb zircon dates of 580–587 Ma from an orthogneiss and an amphibolite are similar to the U–Pb zircon dates of 580–610 Ma from both syntectonic granites in ductile shear zones and high-level posttectonic plutons that intruded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…However, its cessation was diachronous, terminating at ca. 590 Ma in New England (Kaye and Zartman 1980;Zartman 1985, 1992;Thompson et al 1996;Thompson and Bowring 2000), 600 Ma in southern New Brunswick (Bevier and Barr 1990;Barr et al 1994;Currie and McNicoll 1999), 605 Ma in mainland Nova Scotia (Doig et al 1991;Murphy et al 1997;, 575 Ma in southern Cape Breton Bevier et al 1993), 585 Ma in Newfoundland (Krogh et al 1988;O'Brien et al 1996), and 600 Ma in the British Isles (e.g., Tucker and Pharaoh 1991;Horµk 1993;Noble et al 1993).…”
Section: Geologic Settingmentioning
confidence: 99%
“…However, its cessation was diachronous, terminating at ca. 590 Ma in New England (Kaye and Zartman 1980;Zartman 1985, 1992;Thompson et al 1996;Thompson and Bowring 2000), 600 Ma in southern New Brunswick (Bevier and Barr 1990;Barr et al 1994;Currie and McNicoll 1999), 605 Ma in mainland Nova Scotia (Doig et al 1991;Murphy et al 1997;, 575 Ma in southern Cape Breton Bevier et al 1993), 585 Ma in Newfoundland (Krogh et al 1988;O'Brien et al 1996), and 600 Ma in the British Isles (e.g., Tucker and Pharaoh 1991;Horµk 1993;Noble et al 1993).…”
Section: Geologic Settingmentioning
confidence: 99%
“…The fi rst two units occur principally as sheets tens to hundreds of metres thick within the Gamble Brook Formation, with structures indicating emplacement during shearing . Geochronology by 40 Ar/ 39 Ar on hornblende (Keppie et al 1990) and U-Pb on zircon (Doig et al 1991) showed that the Frog Lake gabbro/diorite is about 622 Ma and the Debert River granodiorite 609 -605 Ma. Poor quality U-Pb and Rb-Sr ages of ca.…”
Section: The Bass River Blockmentioning
confidence: 99%
“…Poor quality U-Pb and Rb-Sr ages of ca. 575 Ma (Doig et al 1991) have been obtained from the McCallum Settlement granite unit, which cuts the Debert River granodiorite. In addition, small bodies of the geochemically distinct Glen Road and Gully Brook granite units have been recognised in the Mount Thom area (Pe- .…”
Section: The Bass River Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…The basal contact of the Folly River Formation truncates a mylonitic fabric in the Gamble Brook Formation. A granite, thought to have in truded in the latest stages of the development of this mylo nitic fabric (Nance and Murphy, 1990), yielded aU-Pb zircon age of 605 ± 5 Ma (Doig et al, 1991). Nance and Murphy (1990) attributed the fabric development in the Gamble Brook Formation to sinistral, strike-slip movements during development of the basin into which the Folly River Forma tion was deposited.…”
Section: Cobequid Highlandsmentioning
confidence: 99%